Food safety among students of Secondary School of southeast Mexico - Guzmán Pérez, Sonia Nohemí; Barragán Lizama, Ligia Araceli; Gallegos Gallegos, Rossana Patricia (Horizonte Sanitario, 2019)
Objective. Evaluate food safety among students of the Technical Secondary School 26, Chiltepec, Paraíso, Tabasco. Materials and methods. Descriptive, cross-sectional study; in which 250 students’ parents or tutors of Technical High School 26 participated, located in a rural community of the municipality of Paraíso, Tabasco. The instrument used to evaluate food security was the Latin American and Caribbean Food Security Scale (ELCSA), developed and validated by the Food and Agriculture Organization of the United Nations (FAO). The data analysis was carried out with the Statistical Package for the Social Sciences (SPSS) version 15 software using descriptive statistics. Results. The level of schooling of students’ parents or guardians participating in this study is basic level (47.2%), only 29.6% is working and 69.2% receives an amount less than or equal to 4000.00 per month. Of these students, 86.8% are at some level of food insecurity, with slight food insecurity having the highest prevalence (38.4%) followed by moderate (17.6%). Conclusions. Technical High School students have limited access to food, since most have some degree of food insecurity. Keywords: Food; Food quality; Nutritional status; Malnutrition.